PENGARUH FAKTOR UPAH, USIA, PENDAPATAN SUAMI, USIA ANAK TERAKHIR, DAN PENGELUARAN RUMAH TANGGA TERHADAP CURAHAN JAM KERJA PEREMPUAN MENIKAH DI KOTA MAGELANG - Reikha Habibah Yusfi; Achma Hendra Setiawan (Universitas Diponegoro, 2014)
ABSTRACTBased on data from the Central Statistics Agency of Central Java Province is known that the Labour Force Participation of Women always increase . Married women have multiple roles and that is taking care of the household work . Expansion of employment and real wage increases higher to cause an increase in the labor supply of married women . Labor supply is a function of the wage rate . Magelang City is a city with the second highest outpouring of hours worked in Central Java Province but has a minimum wage smaller compared to other districts/ municipalities who drink fewer working hours .Generally, this study aims to determine the outpouring of working hours of married women in the city of Magelang and some of the factors that influence it. This study uses primary data on 98 respondents . Data were analyzed using ordinary least squre method ( OLS ) , the independent variable is the wage married women , age , husband's income , the age of the last child , and household expenses . Outpouring dependent variable working hours of married women.Results of the study is that wages , child's age and household spending last significant effect on the working hours of married women drink . Wages become the most dominant variable to the outpouring of working hours of married women . While the husband's age and income variables are not significant to the outpouring of the working hours of married women .